Analysis of Factors Contributing to the Lack of Social Care Attitudes Among Children Aged 5–6 Years at Tiberias Kindergarten, Tuak Daun Merah (TDM), Kupang City - Yohanes Argedius Siki; Gokma Nafita Tampubolon; Angelikus Nama Koten (Asian Journal of Applied Education (AJAE), 2026)
This study focuses on identifying the reasons behind the lack of social awareness among children aged 5 to 6 years at Tiberias Kindergarten in Tuak Daun Merah, Kupang City. A descriptive qualitative method was applied, involving semi-structured interviews with five parents and two teachers who were purposively selected and recruited through referrals. The data were analyzed using the interactive model proposed by Miles and Huberman, along with source triangulation. The findings show that low social awareness is influenced by children’s internal characteristics (such as stubbornness and emotional reactivity), family influences (including authoritarian parenting styles and physical punishment), and social environmental factors (such as aggressive interactions with peers). Although the school environment provides some positive effects, it has not yet been fully effective, highlighting the need for collaboration among all stakeholders.